HEMATOLOGICAL PARAMETERS OF T- AND B-CELL IMMUNITY OF CARP BY PHILOMETROIDOSIS - Kostash, V.B.; Kostash, V.B.; Prylipko, T.M.; Koval , T.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
The data of hematological parameters of carp for phylometroidosis are given. During the parasitological examination on the body of the fish revealed swelling, bumps, reddened areas, stiffness of the scales. Pink helminths 8-10 cm long were found in some scaly pockets and muscle tissue. Mature nematodes were more often localized under the scales around the head in the spine, on the sides and abdomen, sometimes on the gill covers, less often they were found on the tail. The obtained data indicate significant changes in hematological parameters of the erythroid blood line of sick and healthy fish. Analysis of the data showed that the number of erythrocytes was significantly higher in clinically healthy fish, but the resistance of erythrocytes was slightly increased in the blood of fish with phylometroidosis. The hematocrit was slightly higher in the blood of clinically healthy fish. There was a slight decrease in the number of T-active lymphocytes in the blood of fish affected by phyllometroidosis by 15.76% (P - 0.01). The same downward trend was found for other indicators, namely T-total lymphocytes by 12.84% (P - 0.01). The indicators of T-helpers (by 17.70%), T-suppressors (by 35.31%) and the values of B-RUL of lymphocytes by 10.55% (P - 0.05) probably decreased.